Synthesis and luminescent properties of uniform monodisperse LuPO4:Eu3+/Tb3+ hollow microspheres. Issue 12 (20th December 2017) - Gao, Yu; Yu, He; Shi, Cheng; Zhao, Guiyan; Bi, Yanfeng; Xu, Baotong; Ding, Fu; Sun, Yaguang; Xu, Zhenhe
Abstract : Uniform monodisperse LuPO4 :Eu 3+ /Tb 3+ hollow microspheres with diameters of about 2.4 µm have been successfully synthesized by the combination of a facile homogeneous precipitation approach, an ion-exchange process and a calcination process. The possible formation mechanism for the hollow microspheres was presented. Furthermore, the luminescence properties revealed that the LuPO4 :Eu 3+ and LuPO4 :Tb 3+ phosphors show strong orange-red and green emissions under ultraviolet excitation, respectively, which endows this material with potential application in many fields, such as light display systems and optoelectronic devices. Since the synthetic process can be carried out at mild conditions, it should be straightforward to scale up the entire process for large-scale production of the LuPO4 hollow microspheres. Furthermore, this general and simple method may be of much significance in the synthesis of many other inorganic materials.